Low-Dose Tirofiban Treatment Improves Neurological Deterioration Outcome After Intravenous Thrombolysis. Issue 12 (December 2019) - Wu, Chuanjie; Sun, Chenghe; Wang, Lijun; Lian, Yajun; Xie, Nanchang; Huang, Shengming; Zhao, Wenbo; Ren, Ming; Wu, Di; Ding, Jianping; Song, Haiqing; Wang, Yuping; et al.
Abstract : Background and Purpose—: Early use of antiplatelet drugs within 24 hours after intravenous thrombolysis (IVT) has always been a confusing clinical problem. The purpose of this study was to assess the safety and efficacy of early low-dose tirofiban treatment in patients with early neurological deterioration (END) within the first 24 hours after IVT. Methods—: This was a retrospective analysis of prospectively collected data of 1764 consecutive patients with acute ischemic stroke treated with IVT between January 2017 and September 2018. Patients with early neurological deterioration within the first 24 hours after IVT were treated with or without tirofiban. The safety outcomes included symptomatic intracranial hemorrhage, any ICH, severe systemic bleeding, and mortality. Efficacy outcomes included excellent (modified Rankin scale scores 0–1) and favorable (modified Rankin scale scores 0–2) 3-month functional outcomes. Results—: Early neurological deterioration occurred in 278 (15.8%) patients. Of the 187 eligible patients, 121 (64.7%) were treated with tirofiban within the first 24 hours after IVT. Adjusted multivariate analysis showed that early tirofiban use was not associated with symptomatic intracranial hemorrhage (adjusted odds ratio [aOR], 1.05; 95% CI, 0.088–11.02; P =1.000), ICH (aOR, 1.13; 95% CI, 0.45–4.25; P =0.512), and mortality (aOR, 0.77; 95% CI, 0.19–2.27; P =0.875) but was significantly associated with excellent (aOR, 2.24; 95% CI, 1.16–3.94; P =0.027) and favorable (aOR, 2.31; 95% CI, 1.48–3.99; P =0.011) functional outcomes. Subgroup analyses suggested that early tirofiban-use efficacy is time dependent, being more effective in patients receiving tirofiban treatment earlier. Conclusions—: Low-dose tirofiban use in patients with early neurological deterioration within the first 24 hours after IVT did not increase the risk of symptomatic intracranial hemorrhage, ICH, and mortality, it seems associated with neurological improvement at 3 months. Future randomized clinical trials will be needed to validate these results.